PROMOSI JASA PERJALANAN HAJI DAN UMROH PADA PT. CAHAYA HATI WISATA RELIGI DI KOTA PEKANBARU PROVINSI RIAU - Meishafa, Khaila; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to determine the promotional strategy for Hajj and Umrah travel services implemented by PT. Cahaya Hati Wisata Religi in Pekanbaru City, Riau Province, and the obstacles encountered in its implementation. Promotion is a crucial aspect of the religious travel industry to attract pilgrims and face market competition. This study used a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. The results indicate that PT. Cahaya Hati Wisata Religi uses four promotional mix tools: advertising (brochures, posters, banners), sales promotion (price discounts and bonus prayer equipment), publicity (media publications and religious events), and personal selling (direct approaches through representatives and communities). Digital promotion through social media such as Instagram, WhatsApp, and YouTube also plays a significant role in increasing marketing reach. Obstacles faced include intense competition among travel agencies, building pilgrim trust, and maintaining service quality. The promotional strategy implemented has helped the company expand its market and strengthen its position in the religious travel services industry. Keywords: Promotion, Travel Services, Hajj and Umrah, PT. Cahaya Hati Wisata Religi, Pekanbaru.